Impact of defects on the structural and electrical transport properties of Sb2Te3 thin films by SHI irradiation - Jyoti Yadav; Rini Singh; M.D. Anoop; Nisha Yadav; N. Srinivasa Rao; Fouran Singh; Kamlendra Awasthi; Manoj Kumar (Materials Letters: X, 2021)
Implantation of defects is an attractive trend for the modification of important properties of thin films for practical applications. In the present attempt, an effective approach for tuning the native defects in thin films is reported. The films were sequentially irradiated at five different fluences (5 × 1011, 1 × 1012, 3 × 1012, 5 × 1012, and 1 × 1013 ions/cm2). The key role of high-energy Ni ion irradiation-induced native defects was observed by the modifications in the physical properties of samples. However, irradiation induces a structural phase transition through strain. The average crystallite size as determined from X-ray diffraction (XRD) peak broadening was found to be 19.3 ± 5 (nm). A monotonic increase in the lattice strain was observed up to a fluence of 5 × 1012 ions/cm2. The resistivity v/s temperature measurements revealed an increase in resistivity up to the fluence 3 × 1012 ions/cm2 indicating an increase in grain boundaries effect. Our findings provide an insight into the correlation of tuned properties with the defects induced by irradiation and also a route to have the defects in a precise and controlled way.